WATER REUSE IN FERTIRRIGATION OF TREATED EFFLUENT, AIMING SOCIO-ENVIRONMENTAL SUSTAINABILITY IN THE REFRIGERATOR’S AREA OF INFLUENCE - da Conceição Rodrigues Pereira, Maria; Valéria Porto de Oliveira Cunha, Márcia (Journal of Interdisciplinary Debates, 2023)
The present work aimed to implement the reuse of water after the treatment of industrial effluents from a slaughterhouse and slaughterhouse, through the projection of reuse fronts, aiming at socio-environmental sustainability in the area of influence of the activity, with the following steps being carried out : preparation of a plan for the implementation of post-treatment effluent reuse points; installation of infrastructure for the redistribution of treated effluent on reuse fronts; laboratory analysis of effluents before, during and after treatment; application of internal audit and elaboration/provision of Environmental Report. The gravity drip irrigation proposal is presented in the infrastructural, georeferential map, and meteorological factors, in the direct and indirect influences of the industrial plant, and the water balance of general liquid effluents was a requirement for reuse action on the property, resulting in fertirrigation, and Applied the type of irrigation as a viable installation model, minimal labor, low cost, and useful in rural and urban areas, adapting to a flat or sloping profile, taking advantage of gravity for distribution. The equalization of the effluent after treatment proposes the quality of the product, raising awareness about the proper destination of said effluents, being important on fronts that do not require drinking water, avoiding waste, having a vision of socio-environmental sustainability, and through controls and monitoring the indicators meet compliance with the standards of relevant laws and regulations.